Factors of Negative Affect in Elderly Patients With Substance Use Disorders During COVID-19 Pandemic - Wang, Qianjin; Wang, Yingying; Zuo, Jinsong; Zhou, Yanan; Yang, Winson Fu Zun; Liao, Yanhui; Tang, Jinsong; Wang, Xin; Yang, Qian; Wu, Qiuxia; Wu, Hanjing Emily; Goodman, Colin B; et al. (Frontiers in Psychiatry, 2021)
Background: The outbreak of the novel coronavirus disease 2019 (COVID-19) has become the greatest public health emergency and has attracted global attention. During the COVID-19 pandemic, the negative affect (NA)of elderly patients with substance use disorders (SUDs) has also become a more serious public concern. The current study aims to clarify the NA and its influencing factors in elderly patients with SUDs during the pandemic. Methods: Two psychiatrists conducted semi-structured interviews with 77 SUD patients aged above 50 years to collect their demographical information and certain drug use characteristics. Barratt Impulse Scale and the Positive and Negative Affect Scale were used to obtain information about patients’ self-reported impulsivity and NA. Results: Univariate linear regression analysis showed that NA was positively correlated with the frequency of drug use, type of SUDs, cravings during COVID-19 and impulsivity. Multiple linear regression analysis showed that being female, higher frequency of drug use, stronger cravings and greater impulsiveness jointly accounted for the variation of NA in elderly patients with SUDs. Conclusions: This study confirmed that, during the COVID-19 pandemic, . gender, frequency of drug use, cravings and impulsivity were associated with NA for in elderly patients with SUDs. This study provided a theoretical basis for clinicians to reduce the patients’ NA.